Pengaruh Influencer dan Fitur Marketplace terhadap Purchase Behavior dengan Purchase Intention sebagai Variabel Intervening pada TikTok Shop - Alfiatun Nikmah; Alifah Ratnawati (ARZUSIN, 2026)
The growth of social media–based e-commerce has driven changes in consumer purchasing behavior, particularly through TikTok Shop, which integrates entertainment content, influencers, and marketplace features. However, the high number of users does not always correspond to actual purchasing behavior, creating a gap between purchase intention and purchase behavior. This study aimed to analyze the influence of influencers and marketplace features on purchase behavior, with purchase intention as an intervening variable among TikTok Shop users. A quantitative method with an explanatory research approach was employed, involving 96 respondents selected through purposive sampling based on the criterion of having made at least three purchases via TikTok Shop. Data were collected using an online questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. The results showed that influencers and marketplace features had a positive and significant effect on purchase intention. In addition, influencers, marketplace features, and purchase intention had a positive and significant effect on purchase behavior, and purchase intention functioned as an intervening variable mediating the influence of influencers and marketplace features on purchase behavior. These findings confirm that increased consumer purchase behavior on TikTok Shop is driven by the effectiveness of influencers and the utilization of marketplace features that can enhance purchase intention and convert it into actual purchases. The implications of this study provide recommendations for business practitioners to optimize digital marketing strategies through collaboration with influencers and the use of live streaming and online customer reviews to increase purchase conversion.